Adjunctive ondansetron for schizophrenia: A systematic review and meta-analysis of randomized controlled trials. (June 2019) - Zheng, Wei; Cai, Dong-Bin; Zhang, Qing-E.; He, Jie; Zhong, Li-Yun; Sim, Kang; Ungvari, Gabor S.; Ning, Yu-Ping; Xiang, Yu-Tao
Abstract: The serotonin 5-hydroxytryptamine type 3 (5-HT3) receptor has been implicated in the pathogenesis of schizophrenia. This meta-analysis of randomized controlled trials (RCTs) examined the efficacy and safety of adjunctive ondansetron, a potent 5-HT3 receptor antagonist, in the treatment of schizophrenia. Only RCTs examining adjunctive ondansetron for schizophrenia were included. Standardized mean difference (SMD), risk ratio (RR) and their 95% confidence intervals (CIs) were analyzed using RevMan, Version 5.3. Study quality was evaluated with the Cochrane risk of bias and the Jadad scale. Data of 5 RCTs (n = 304) covering 149 patients on ondansetron (4-8 mg/day) and 155 patients on placebo were analyzed. Three RCTs reported "randomized allocation" with a specific description; the weighted Jadad score was 3.8. Adjunctive ondansetron outperformed placebo in the reduction of Positive and Negative Syndrome Scale (PANSS) total score [3 RCTs, n = 171; SMD: −1.06 (95%CI: −2.10, −0.02), p = 0.04, I 2 = 85%], the negative [4 RCTs, n = 209; SMD: −0.96 (95%CI: −1.71, −0.22), p = 0.01, I 2 = 80%], and general psychopathology symptom scores [3 RCTs, n = 171; SMD: −0.97 (95%CI: −1.91, −0.02), p = 0.04, I 2 = 82%], but not in the positive (p = 0.05) and depressive symptom scores (p = 0.91). The difference in PANSS total score remained significant after excluding one outlying RCT [2 RCTs, n = 141; SMD: −0.50 (95%CI: −0.84, −0.16), P = 0.004, I 2 = 0%]. Four RCTs examined the effect of ondansetron on cognition applying different instruments yielding conflicting findings. Ondansetron was superior over placebo in improving extrapyramidal symptoms, but no group differences were found in overall discontinuation rate and adverse drug reactions. In conclusion, adjunctive ondansetron appears to be efficacious and safe in improving negative symptoms and general psychopathology. The effect of ondansetron on cognitive impairment in schizophrenia needs to be further explored in large-scale RCTs. Highlights: Ondansetron, a potent 5-HT3 receptor antagonist, has been used in treating schizophrenia, with conflicting results. Adjunctive ondansetron appears to be efficacious and safety in improving negative symptoms and general psychopathology. The effect of ondansetron on cognitive impairment in schizophrenia needs to be further examined in large-scale prospective studies.